Gambaran Schizencephaly dengan Polymicrogyria pada Berbagai Magnetic Resonance Imaging (MRI) Sekuens - Tanaji, Tandy; Hendara, Farah; Marliana, Caecilia; Astien, Astien; Nareswari, Gupita; Napitupulu, Partogi; Rahmansyah, Mulia; Wahab, Revalita (Fakultas Kedokteran Universitas Trisakti, 2025)
Schizencephaly is a rare congenital cerebral malformation within the category of neurological migration defects. Hemiparesis, developmental delays, and seizures are clinical signs that are influenced by both the size and the location of the lesion. This condition is characterized by a cleft that traverses the brain's parenchyma lined by grey-mater (transmantle cleft). In less severe cases, the cleft does not extend into the lateral ventricle. Identification of the cleft's path, accurate assessment of the cortex, and recognition of polymicrogyria are crucial for the radiological evaluation of schizencephaly. We report a case of 18-year-old male diagnosed with closed-lip schizencephaly, which supported by MRI findings. The transmantle cleft and polymicrogyria are most effectively visualized in T2-weighted and FLAIR images. The utility of diffusion-weighted imaging (DWI) and apparent diffusion coefficient (ADC) sequences as well as susceptibility-weighted imaging (SWI) sequence in the context of schizencephaly currently remains uncertain, however it may be useful for ruling out other abnormalities such infarct, hemorrhagic, tumors or other vascular abnormalities. In this context, we emphasize the significance of MRI examination for diagnosing this condition and for recognizing the related abnormalities.